Growth and mortality of sympatric white‐tailed and mule deer fawns. Issue 8 (4th August 2017) - Haskell, Shawn P.; Ballard, Warren B.; Mcroberts, Jon T.; Wallace, Mark C.; Krausman, Paul R.; Humphrey, Mary H.; Alcumbrac, Ole J.; Butler, David A.
ABSTRACT: Population growth rates of cervids are sensitive to changes in adult female survival, but fawn recruitment tends to be the population vital rate most susceptible to density‐dependent population‐level influences. We conducted a study of fawn survival rates and related biology in northwest Crockett County, Texas, USA, during 2004–2007 in an area where white‐tailed deer ( Odocoileus virginianus ) and mule deer ( O. hemionus eremicus ) existed sympatrically. Our fawn study was justified by the need to explain annual variation in female‐to‐fawn ratios apparent during field surveys. Using vaginal implant transmitters in radio‐marked adult females to locate birth sites, we captured, weighed, and radio‐collared fawns on 4 privately owned ranches. We monitored collared fawns daily and investigated mortalities within 24 hours of receiving a mortality signal to determine cause of death. When possible, we collected thymus glands to assess body condition. We captured 170 fawns (64 white‐tailed deer; 106 mule deer), of which 145 were of known‐age from collared females, and found that relatively heavy adult females birthed relatively heavy fawns. We also noted that mass gain of fawns and mass of fawns' thymus glands were very low compared to other studies of fawns. We documented mortalities: 47 by predation, 47 by sickness‐starvation, 1 by conspecific trauma, and 3 undeterminable. Bobcats ( Lynx rufus ) were responsible for nearly all fawn predation; thymus gland and fawn mass data indicated that bobcats did not select weaker fawns. We used proportional hazards regression to assess factors influencing fawn survival and competing risks of mortality and made comparisons between the species when possible. We censored 6 fawns from our analyses and found that half of mortalities occurred within 15 days postpartum, and 12 of the 139 known‐age fawns (9%) died within 25 m of the birth site. Fawn survival was 78% at 6 days old, which was the median estimated age‐at‐capture of fawns from unknown adults. Annual fawn survival rate ranged from 50% for fawns born in 2004 to 17% for fawns born in 2006, with no overall effect of species. Fawn survival was greatest in 2004 when rain during the May–August late‐gestation and lactation period was greatest. Mule deer fawns succumbed more to sickness‐starvation than did white‐tailed deer fawns. Rates of sickness‐starvation and predation increased with deviance from mean annual birth dates and with reduced rain during the late‐gestation and lactation period. Early fawn survival increased with relative fawn mass, and sex became important at about 30 days postpartum, after which males were at greater risk of sickness‐starvation. Lunn‐McNeil competing‐risks models suggested some interaction between sickness‐starvation and predation. Fawn mortality, mass gain, thymus mass, and weaning data indicated that the populations of both deer species were chronically stressed near a carrying capacity that fluctuated annually with rain and that adult females invested little energy in rearing fawns relative to captive females. © 2017 The Wildlife Society. Abstract : Understanding the links between periodic or regular resource limitations, measures of nutritional conditions, and vital rates of cervid populations can be important to wildlife and habitat managers. Data from fawn mortality, thymus glands, body mass gain, and weaning dates indicated that populations of white‐tailed deer and mule deer were chronically stressed near a carrying capacity that responded to rain and that females invested relatively little energy rearing fawns.